Prognostic significance of epicardial adipose tissue in heart failure with preserved and reduced ejection fraction. (14th October 2021) - Pugliese, N.R; De Biase, N; Mazzola, M; Paneni, F; Del Punta, L; Gargani, L; Mengozzi, A; Virdis, A; Nesti, L; Taddei, S; Flammer, A; Borlaug, B.A; et al.
Abstract: Background: Increased epicardial adipose tissue (EAT) thickness correlates with metabolic syndrome, insulin resistance, microvascular dysfunction and enhanced pericardial restraint. Purpose: We measured echocardiographic EAT thickness in heart failure (HF) patients with reduced (HFrEF) or preserved (HFpEF) ejection fraction to determine whether EAT could bear prognostic significance at clinical follow-up. Methods: We prospectively enrolled 393 consecutive HF outpatients (205 HFrEF, 188 HFpEF) referred to our hospital due to dyspnoea and/or effort intolerance. We performed a resting clinical and biohumoral evaluation, followed by combined cardiopulmonary-echocardiography exercise stress. A composite of cardiovascular death and HF-related hospitalization was chosen as endpoint during follow-up. Results: Patients with HFpEF displayed higher EAT thickness (median 8 mm, interquartile range [IQR] 4–12 mm) than HFrEF (median 3 mm, IQR 2–6 mm; p<0.0001). During a median follow-up of 20.9 months (IQR 15–25 months), we reported 34 cardiovascular deaths and 146 HF hospitalizations, with no significant differences between the two HF subsets. EAT predicted adverse events independently from body mass index and well-established markers of poor prognosis (e.g., NT-proBNP, peak oxygen consumption). The risk of adverse events increased with increasing EAT thickness in HFpEF and with EAT thinning in HFrEF. Kaplan-Meier analyses for the composite endpoint showed that in HFpEF, the survival probability was significantly lower in patients with thicker EAT than those with thinner EAT. In HFrEF, conversely, patients with thicker EAT had a higher survival probability than those with reduced EAT thickness (Figure 1). Conclusion: EAT accumulation is more marked in HFpEF than HFrEF and carries different prognostic meanings in the two subsets. In HFpEF, EAT thickening portends adverse outcome, which may be due to increased mechanical restraint and secretion of pro-inflammatory and pro-atherogenic adipokines. In HFrEF, greater EAT thickness seems to have a protective role, while EAT thinning is associated with a worse prognosis, likely reflecting a catabolic state (i.e. cardiac cachexia). Larger studies will clarify whether EAT is a bystander or an active player in the different HF phenotypes. Funding Acknowledgement: Type of funding sources: None.